A giant radio flare from Cygnus X-3 with associated ?-ray emission - Corbel, S.; Dubus, G.; Tomsick, J. A.; Szostek, A.; Corbet, R. H. D.; Miller-Jones, J. C. A.; Richards, J. L.; Pooley, G.; Trushkin, S.; Dubois, R.; Hill, A. B.; Kerr, M.; et al. (Monthly Notices of the Royal Astronomical Society, 2012)
With frequent flaring activity of its relativistic jets, Cygnus X-3 (Cyg X-3) is one of the most active microquasars and is the only Galactic black hole candidate with confirmed high-energy ?-ray emission, thanks to detections by Fermi Large Area Telescope (Fermi/LAT) and AGILE. In 2011, Cyg X-3 was observed to transit to a soft X-ray state, which is known to be associated with high-energy ?-ray emission. We present the results of a multiwavelength campaign covering a quenched state, when radio emission from Cyg X-3 is at its weakest and the X-ray spectrum is very soft. A giant (similar to 20 Jy) optically thin radio flare marks the end of the quenched state, accompanied by rising non-thermal hard X-rays. Fermi/LAT observations (E= 100 MeV) reveal renewed ?-ray activity associated with this giant radio flare, suggesting a common origin for all non-thermal components. In addition, current observations unambiguously show that the ?-ray emission is not exclusively related to the rare giant radio flares. A three-week period of ?-ray emission is also detected when Cyg X-3 was weakly flaring in radio, right before transition to the radio quenched state. No ?-rays are observed during the similar to 1-month long quenched state, when the radio flux is weakest. Our results suggest transitions into and out of the ultrasoft X-ray (radio-quenched) state trigger ?-ray emission, implying a connection to the accretion process, and also that the ?-ray activity is related to the level of radio flux (and possibly shock formation), strengthening the connection to the relativistic jets.
Keywords: black hole physics; stars: individual: Cyg X-3; ISM: jets and outflows; gamma-rays: stars; radio continuum: stars; X-rays: binaries